Ultrasound Scanning as a Technique in Pregnancy Diagnosis of Saanen Breed at UniSZA Dairy Goat Farm - Ramli, Abdullah; Asmad, Kari; Wan Khadijah, Wan Embong; Nur Diyana, Abdullah (2018)
Ultrasonography is not only commonly used in human but also is a useful tool for diagnosis of pregnancy in livestock species, including goats. It was improved with the advent of real-time B-mode (brightness mode) imaging. This tool was used more frequently in sheep compared with goats. The present study was conducted to use B-mode transabdominal probes development of goat pregnancy scanning protocol in UniSZA Dairy Goat Farm (UDGF). Ultra-structure images at different stages of pregnancy and the earliest possible diagnosis of pregnant does were determined. The results of this study showed the following structures: embryonic sacs (days 28-48), foetal (days 28-52), foetal head (days 56-144) and placentome (days 40-146). Single and twin foetuses were differentiated after 56 days of estimated pregnancy. The efficacy of this project was determined based on the frequency of occurrence of the ultra-structures that have been observed. Ultra-structures detected by ultrasound scanner have been identified as indicators for foetal twinning and as a predictor to differentiate stages of pregnancy. In a nutshell, the data of ultra-structures were analysed by percentages of whole stages of pregnancy to detect early pregnancy, twinning of foetus as well as detection of pregnancy. The outcomes of this research will be the fundamental scientific information that could be applied practically as an integrated component of goat management practices in the dairy goat industry for income generation and small farmers in the rural areas for their wellbeing and livelihood as well as for food security and safety of this country.